Purification of Zinc Oxide Using Direct Thermal Process by Petroleum Coke - K. Al-Dawery, Salam; A-A. Khammas, Zuhair; Adnan Abdulla, Thaer (Iraqi Journal of Chemical and Petroleum Engineering, 2009)
The present investigation is concerned for the purification of impure zinc oxide (80-85 wt %) by using petroleum coke (carbon content is 76 wt %) as reducing agent for the impure zinc oxide to provide pure zinc vapor, which will be oxidized later by air to the pure zinc oxide. The operating conditions of the reaction were studied in detail which are, reaction time within the range (10 to 30 min), reaction temperature (900 to 1100 oC), air flow rate (0.2 to 1 l/min) and weight percentage of the reducing agent (petroleum coke) in the feed (14 to 30 wt %). The best operating conditions were (30 min) for the reaction time, (1100 oC) for the reaction temperature, (1 l/min) for the air flow rate, and (30 wt %) of reducing material (petroleum coke) in the feed. Under the above conditions, conversion of zinc oxide was (68.12 %) and the purity of the produced zinc oxide was (97.85 %) by using petroleum coke as reducing material.